Comparing the Opportunities Provided by Altmetrics and Citation Analysis for Research Evaluation - Hajar; Masoumeh; Mahdieh Mirzabegi (Iranian Journal of Information Processing & Management, 2018)
The present study atempts to explain the strengths of altmetrics and compare them with those of citation-based indicators, and thereby reveal opportunities provided by social web in research evaluation. Applying a qualitative thematic analysis method, it studied the contents of research and theoretical works about the citation and altmetrics indicators in order to extract their authors’ views about the indicators’ strengths. The findings led to the identification of many strengths of altmetrics compared to the citation analysis including openness and ease of access, non-dependence on commercial databases, impact assessment of preprints, measuring different types of research impact, promoting peer-review processes, reducing language biases, impact assessment of young researchers, accelerating the evaluation process, calculating the impacts on all kinds of audiences, predicting the future research impact, evaluating the impact of uncited papers, inter-disciplinary comparisons, evaluating a wide variety of sources and researchers’ outputs, and analyzing low-cited or slowly-cited subjecs. Althougth both indices have many strengths, altmetrics has more that can compensate for the weaknesses of citation analysis. As a result, using them together can make the results of research evaluation more reliable and increase their accuracy and precision.